Ciphertext-only fault analysis of the TWINE lightweight cryptogram algorithm - Wei LI; Menglin WANG; Dawu GU; Jiayao LI; Tianpei CAI; Guangwei XU (Tongxin xuebao)
The security analysis of TWINE against the ciphertext-only fault analysis was proposed.The secret key of TWINE could be recovered with a success probability at least 99% using a series of distinguishers of SEI、MLE、HW、GF、GF-SEI、GF-MLE、Parzen-HW、MLE-HE、HW-HE and HW-MLE-HE.Among them, the novel proposed distinguishers of MLE-HE、HW-HE and HW-MLE-HE can effectively reduce the faults and improve the attack efficiency in simulating experiments.It provides a significant reference for analyzing the security of lightweight ciphers in the Internet of Things.